Responding to COVID-19 pandemic from Islamic perspective - Ahmad, Zeti Azreen (2020)
COVID-19 pandemic is one of the worst health crises since the beginning of the 21st century. In less than four months, the new coronavirus or known as COVID-19 has affected almost 3 million people and the death toll exceeds 200,000 worldwide (Ministry of Health, 27 April 2020). The infectious disease has put many countries on lockdown to break the chain of infection. Malaysian is not spared in this devastating health crisis. In the second wave of the outbreak, the government has implemented a partial lockdown nationwide or known as the movement control order (MCO) to reduce the number of new cases and subsequently flatten the curve. This paper aims to address the value responding appropriately in the midst of adversity such as COVID-19 pandemic from the Islamic perspective. It is worth noting that how we respond to this pandemic will make a big difference not only to ourselves but also to others.